Understanding Civil War: Evidence and Analysis - Collier, P (World Bank, 2005)
Ten papers combine large-N quantitative empirical analysis with comparative case studies to develop the theory of civil war. Papers use the quantitative Collier-Hoeffler model of civil war to analyze a comprehensive data set of civil wars over the period 1960-99 and present case studies focusing on resources and rebellion in Aceh, Indonesia; the Lebanese civil war, 1975-90; crime, violence, and political conflict in Russia; conflict, violence, and crime in Colombia; the "troubles" of Northern Ireland; Bosnia's civil war; how Macedonia avoided civil war, 1990-2001; and civil wars in the Caucasus. A final paper synthesizes lessons and insights from the cases, uses the insights to suggest possible revisions and refinements to the Collier-Hoeffler model, and identifies a number of ways in which the theory of civil war can be expanded. Most of the contributors are either economists or political scientists. Collier is at Oxford University and its Center for the Study of African Economies. Sambanis is at Yale University. Index.